Biological Effects of Osteopontin on Endothelial Progenitor Cells - Altalhi, Wafa (Université d'Ottawa / University of Ottawa, 2011)
Endothelial Progenitor Cells (EPCs) are thought to participate in the healing of injured vascular endothelium by incorporating into the defect sites to mediate endothelial recovery. Recently, osteopontin (OPN) was shown to be fundamental in accelerating estrogen-dependent healing of injured blood vessels. Here, we are investigating the effect OPN has on EPC behavior. Late outgrowth human EPCs (LEPCs) were derived from circulating monocytes isolated by leukophoresis, and grown in culture until passage six. L-EPCs were then assayed for adhesion, spreading, chemotaxis, and haptotaxis, as well as resistance to detachment by flow electric cellsubstrate impedance sensing (ECIS). The results of standard and ECIS methods showed both dose and time dependent responses in cell adhesion and spreading. In addition, OPN promoted haptotactic migration of EPCs in Boyden chamber assays. LEPCs seeded onto 10μM OPN substrates and exposed to laminar flow had grater survival and higher resistance to detachment than OPN/static and flow only conditions. CD44 and !1 integrins were only responsible for approximately 50% of LEPCs adhesion to OPN compared to the unblocked condition. Western blots showed that Rho GTPases were activated in L-EPCs seeded on OPN. However, this activation could not be completely blocked by either CD44 or !1 integrin antagonists. These data confirm the direct effects of OPN on EPCs adhesion, and suggest that OPN works by mediating cell adhesion during vascular injury.
Keywords: Endothelium; Integrins; EPC; OPN; Osteopontin; Endothelial progenitor cells